2023
DOI: 10.3390/atmos14030497
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Crop Management Practices and Adaptation Options to Minimize the Impact of Climate Change on Maize (Zea mays L.) Production for Ethiopia

Abstract: Climate change impact assessment along with adaptation measures are key for reducing the impact of climate change on crop production. The impact of current and future climate change on maize production was investigated, and the adaptation role of shifting planting dates, different levels of nitrogen fertilizer rates, and choice of maize cultivar as possible climate change adaptation strategies were assessed. The study was conducted in three environmentally contrasting sites in Ethiopia, namely: Ambo, Bako, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Since maize is the most modeled crop in Ethiopia using the APSIM system, lots of locally grown cultivars are tested in different years. The tested cultivars consisted of both late, medium, and early-growing cultivars such as BH546, BH661, Jibat, and MH140 [ 23 , 24 ], BH660 [ 25 ], Melkassa-1, BH660Q [ 20 ], MH19, BH660, Katumani, and Melkassa-2 [ 26 ], BH540, BH543, BH546, MH130, SC403, and TH13321 [ 27 ], Melkassa-2 [ 28 ], early growing SC401, medium growing SC625, and late growing SC709 [ 29 , 30 ] were used for APSIM maize calibration and validation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since maize is the most modeled crop in Ethiopia using the APSIM system, lots of locally grown cultivars are tested in different years. The tested cultivars consisted of both late, medium, and early-growing cultivars such as BH546, BH661, Jibat, and MH140 [ 23 , 24 ], BH660 [ 25 ], Melkassa-1, BH660Q [ 20 ], MH19, BH660, Katumani, and Melkassa-2 [ 26 ], BH540, BH543, BH546, MH130, SC403, and TH13321 [ 27 ], Melkassa-2 [ 28 ], early growing SC401, medium growing SC625, and late growing SC709 [ 29 , 30 ] were used for APSIM maize calibration and validation.…”
Section: Resultsmentioning
confidence: 99%
“…Among the different researchers surveyed in this study, Refs. [ 24 , 28 ] used these input data to investigate the effects of different management practices, i.e., fertilizer rate, fertilizer application time, and water amount, and water application times. While other researchers, Refs.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that SDs and cultivars are the main agronomic practices influencing the maize yield dynamics acting independently and in their interactions in the region. SDs and other farm management decisions determine the intersection of critical phenological stages with favorable weather conditions (Feleke et al., 2023; Perondi et al., 2019). Maize requires sufficient precipitation during the tasseling, pollination, silking, and grain stages (Ramirez‐Cabral et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The critical phenological stages with favorable weather conditions (Feleke et al, 2023;Perondi et al, 2019). Maize requires sufficient precipitation during the tasseling, pollination, silking, and grain stages (Ramirez-Cabral et al, 2017).…”
Section: Influence Of Agronomic Practicesmentioning
confidence: 99%
See 1 more Smart Citation